Mineralized agar-based nanocomposite films: Potential food packaging materials with antimicrobial properties. (1st November 2017) - Malagurski, Ivana; Levic, Steva; Nesic, Aleksandra; Mitric, Miodrag; Pavlovic, Vladimir; Dimitrijevic-Brankovic, Suzana
Highlights: Agar was impregnated with Zn-minerals to produce nanocomposite films. Nanocomposites exhibited different morphologies, properties and functionality. Reinforcing with minerals improved mechanical, optical and thermal properties. Nanocomposite films release Zn(II) inducing antimicrobial effect. Abstract: New mineralized, agar-based nanocomposite films (Zn-carbonate and Zn-phosphate/agar) were produced by a combination of in situ precipitation and a casting method. The presence of minerals significantly influenced the morphology, properties and functionality of the obtained nanocomposites. Reinforcement with the Zn-mineral phase improved the mechanical properties of the carbonate-mineralized films, but had a negligible effect on the phosphate-mineralized samples. Both nanocomposites showed improved optical and thermal properties, better Zn(II) release potential in a slightly acidic environment and exhibited antimicrobial activity against S. aureus . These results suggest that Zn-mineralized agar nanocomposite films could be potentially used as affordable, eco-friendly and active food packaging materials.